1977
DOI: 10.1113/jphysiol.1977.sp011959
|View full text |Cite
|
Sign up to set email alerts
|

Active Na—K transport and the rate of ouabain binding. The effect of insulin and other stimuli on skeletal muscle and adipocytes

Abstract: SUMMARY1. The effect of stimulation or inhibition of active Na-K transport on [3H]ouabain binding has been investigated in isolated soleus muscles and adipocytes.2. In rat soleus muscle, the ouabain-sensitive component of 42K influx was stimulated by insulin (100 m-u/ml.), adrenaline (6 x 106 M), and by pre-incubation with veratrine (10-5 M) or in a K-free buffer. In all of these instances, the rate of ouabain binding was increased by 41-113%. Conversely, pre-treatment with tetracaine (0.2 mM) decreased the 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(71 citation statements)
references
References 17 publications
6
65
0
Order By: Relevance
“…In the control muscles a site number of 624 + 19 p-mole . g wet wt.-1 was found, a value slightly above that reported earlier (Clausen & Hansen, 1977). The site number was modified in muscles from hypothyroid and hyperthyroid animals in the same proportion as AJ42K.…”
supporting
confidence: 60%
“…In the control muscles a site number of 624 + 19 p-mole . g wet wt.-1 was found, a value slightly above that reported earlier (Clausen & Hansen, 1977). The site number was modified in muscles from hypothyroid and hyperthyroid animals in the same proportion as AJ42K.…”
supporting
confidence: 60%
“…The fact that hypoinsulinemia causes a decrease in Na + -K + -ATPase activity was not unanticipated. From pioneering work of Clausen and Hansen (7) and Moore (8), it has been well-recognized that insulin stimulates Na + -K + -ATPase in various tissues (2,(7)(8)(9). Insulin, along with catecholamines, is considered to be the principal mediator of acute hormonal control of Na + -K + -ATPase (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although this change is difficult to interpret, insulin appears to play an important role in sodiumpotassium transport in a number of tissues. Insulin receptor density in monocytes increases as a result of training (39); Although the specific effect of endurance training on insulin receptors has not been studied in muscle, studies on skeletal muscle of various species have shown that independently of glucose, insulin hyperpolarizes cells (40), stimulates K uptake (41), increases Na,K-ATPase activity (42), augments [3H]-ouabain binding (43), enhances affinity of pump sites on the inner membrane surface to sodium ions (44,45), and may multiply pump sites (46). Most recently, evidence has been cited that insulin facilitates Na'-proton exchange (47), allowing Na' to stimulate the pump, which generates electronegativity.…”
Section: Discussionmentioning
confidence: 99%